The biography of chocolate - Morganelli, Adrianna , 1979- (How did that get here?, 2006)
All about chocolate: where it comes from, how it's made, how it gets to the store. Provides a history of the popular cacao-derived food, describing the evolution of chocolate's production and usage from Mayan times to the present day.